2014
DOI: 10.7732/kjpr.2014.27.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvest Time on the Several Phenolic Compounds and Fruit Quality of Grape Cultivars

Abstract: -This study was accomplished to investigate the effect of harvest time on the contents of polyphenolic compounds such as epicatechin, catechin, resveratrol and quercetin in grapes (Vitis spp.). The souble solids contents were increased with harvest time delay, while the titratable acidity continuously decreased in all cultivars. Brightness (L) was higher in 'Campbell Early' and 'Shigyoku', Hunter a value was high in 'Shigyoku' which was harvested later. Hunter b value seemed to be different in 'Shigyoku' depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
(1 reference statement)
0
1
0
1
Order By: Relevance
“…Girdling was effective in increasing the vine productivity and berry quality. The results are accordant with that reported by Myriathoasis (1966), Novello et al (1999, Ezzahouani (2000), Yahuaca et al (2006) Lee et al (2010), AbuZahra (2010), Koshita et al (2011), Ferrara et al (2014 Belal ( 2016) Gawankar et al (2019) and El-Salhy et al (2021). They demonstrated that girdling had great impact on vine productivity and improving berry quality of various grape cultivars.…”
Section: Discussionsupporting
confidence: 89%
“…Girdling was effective in increasing the vine productivity and berry quality. The results are accordant with that reported by Myriathoasis (1966), Novello et al (1999, Ezzahouani (2000), Yahuaca et al (2006) Lee et al (2010), AbuZahra (2010), Koshita et al (2011), Ferrara et al (2014 Belal ( 2016) Gawankar et al (2019) and El-Salhy et al (2021). They demonstrated that girdling had great impact on vine productivity and improving berry quality of various grape cultivars.…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Lee et al (2014) To examine the antioxidant activity of S. japonica, ABTS and DPPH assays were conducted. ABTS is widely used to measure the antioxidant activity of natural materials, and the produced ABTS cation reacts with an antioxidant to decolorize the blue-green color, and the antioxidant activity can be evaluated by measuring its absorbance.…”
mentioning
confidence: 99%
“…안토시아닌은 인체의 산화적인 스트레스를 억제하는데 효 과가 있는 것으로 보고됨과 더불어 항암 및 항염증과 관련된 연구 가 활발히 진행되고 있다 (Skoczyñska et al, 1974;Malik et al, 2003;Lee and Jung, 2015). 안토시아닌은 함유된 식물에 따라 각 기 다른 성분특성을 나타내는 것으로 알려져 있으며 포도 (Lee et al, 2014), 옥수수 수염 (Ku et al, 2009), 오디 (Jang and Park, 2013), 꽃베고니아 (Degenhardt et al, 2000), 자색고구마 (Wang et al, 2011), 유색곡물 (Sun et al, 2012;Kang et al, 2003 ◆, control; ■, 50 mmol citric acid is added at 40℃; ▲, 50 mmol citric acid is added at 65℃; ×, 50 mmol citric acid is added at 85℃.…”
unclassified